A comparison of the effects of infliximab, adalimumab, and pentoxifylline on rats with non-alcoholic steatohepatitis - Yalcin, Mustafa; Akarsu, Mesut; Celik, Aslı; Sagol, Ozgul; Tunali, Sunay; Ertener, Ozge; Bengi, Göksel; Akpinar, Hale (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Non-alcoholic steatohepatitis (NASH) lacks effective medical treatment.Since tumor necrosis factor alpha (TNF-α) plays an important role in NASH pathogenesis, we aimed to investigate drugs affecting TNF-α as possible treatment options during the development of NASH. Materials and Methods: A total of 35 rats were divided into five groupsand evaluated over a 6week period. One group received a normal diet alone or in combination with the administration of infliximab, adalimumab or pentoxifylline Results: NASH was successfully established in the MCD diet group. Levels of TNF-α were effectively suppressed in the three groups that received anti-TNF agents. No statistically significant differences were observed between the three agents in terms of the histological NASH score. Conclusion: Our study showed that the anti-TNF agents infliximab, adalimumab, and pentoxifylline effectively suppress TNF-α. Although these drugs did not prevent the development of NASH, they were able to slightly reverse the NASH histopathology score and positively affect liver function tests.